2021
DOI: 10.1002/jwmg.22043
|View full text |Cite
|
Sign up to set email alerts
|

Mule Deer Migrations and Highway Underpass Usage in California, USA

Abstract: Roadways may pose barriers to long‐distance migrators such as some ungulates. Highway underpasses mitigate wildlife‐vehicle collisions and can be an important management tool for protecting migration corridors. In northern California, 3 underpasses were built on United States Route 395 (Route 395) in Hallelujah Junction Wildlife Area (HJWA) in the 1970s for a migratory mule deer (Odocoileus hemionus) herd that had been negatively affected by highway traffic. To determine whether these underpasses were still re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The results from these wildlife crossings have been encouraging. Monitoring studies have shown a significant decrease in wildlife-vehicle collisions in areas where these crossings are present [39]. Furthermore, they have contributed to maintaining genetic diversity within wildlife populations by allowing for greater movement and interaction among separate groups [38].…”
Section: Road Safetymentioning
confidence: 99%
“…The results from these wildlife crossings have been encouraging. Monitoring studies have shown a significant decrease in wildlife-vehicle collisions in areas where these crossings are present [39]. Furthermore, they have contributed to maintaining genetic diversity within wildlife populations by allowing for greater movement and interaction among separate groups [38].…”
Section: Road Safetymentioning
confidence: 99%
“…Anthropogenic barriers (henceforth, “barriers,” e.g., fences, reservoirs, and roads), coinciding with land‐use, development, and management practices, are ubiquitous and increasing worldwide, posing threats to animal movements and their ability to access resources (Jakes et al, 2018; McInturff et al, 2020; Van Moorter et al, 2020). Barriers that are impossible or difficult to cross can result in additional energy expenditure, injury, or direct mortality (e.g., drownings, fence entanglements, and vehicle collisions; Caldwell & Klip, 2021; Harrington & Conover, 2006; Rautenstrauch & Krausman, 1989; Rey et al, 2012). These effects can be exacerbated during times of abnormally severe environmental conditions, such as heavy snowfall or drought (Van Moorter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%